PERIODS OF TRANSITION OF PHENOLOGICAL PHASES OF APPLE VARIETIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article presents data on the analysis of growth phenophases in local and introduced apple varieties in the conditions of the Tashkent region, Information is provided on the summer Pristin, which begins the growth period the latest (16-18/III), the early autumn Kandil Sinap, Bolazhon, Israil, Prikubanskoe, Limonny, Renora winter varieties II-X-31 hybrid, the autumn Kubanskoe Bagryanoe, winter Fuji varieties, the flowering phase begins the latest (8-10/IV) Israil, Limonny, Prikubanskoe and Renora winter varieties, and the earliest (13-17/VII) ripening varieties Kizil Jonaki, Mantet, Stark Erlist, and the latest (24/IX) ripening winter Goldrash varieties.